Thursday, April 9, 2009

Beauty of Mathematics !!!!!!!

-----------------------------------------------------------------------------------------------
1 x 8 + 1 = 9

12 x 8 + 2 = 98

123 x 8 + 3 = 987

1234 x 8 + 4 = 9876

12345 x 8 + 5 = 98765

123456 x 8 + 6 = 987654

1234567 x 8 + 7 = 9876543

12345678 x 8 + 8 = 98765432

123456789 x 8 + 9 = 987654321
-----------------------------------------------------------------------------------------------
1 x 9 + 2 = 11

12 x 9 + 3 = 111

123 x 9 + 4 = 1111

1234 x 9 + 5 = 11111

12345 x 9 + 6 = 111111

123456 x 9 + 7 = 1111111

1234567 x 9 + 8 = 11111111

12345678 x 9 + 9 = 111111111

123456789 x 9 +10= 1111111111
-----------------------------------------------------------------------------------------------
9 x 9 + 7 = 88

98 x 9 + 6 = 888

987 x 9 + 5 = 8888

9876 x 9 + 4 = 88888

98765 x 9 + 3 = 888888

987654 x 9 + 2 = 8888888

9876543 x 9 + 1 = 88888888

98765432 x 9 + 0 = 888888888
-----------------------------------------------------------------------------------------------

Brilliant, isn't it?

And look at this symmetry:

1 x 1 = 1

11 x 11 = 121

111 x 111 = 12321

1111 x 1111 = 1234321

11111 x 11111 = 123454321

111111 x 111111 = 12345654321

1111111 x 1111111 = 1234567654321

11111111 x 11111111 = 123456787654321

111111111 x 111111111 = 12345678987654321

-----------------------------------------------------------------------------------------------
Can you equate 3 and 2 by some mathematics logic?

See this illustration:

-6 = -6

9-15 = 4-10

9-15+25/4 = 4-10+25/4

Changing the order

9+25/4-15 = 4+25/4-10

(this is just like a square + b square - two a b = (a-b)square.)

Here a = 3, b=5/2 for L.H.S and a =2, b=5/2 for R.H.S.

So it can be expressed as follows:

(3-5/2)(3-5/2) = (2-5/2)(2-5/2)

Taking positive square root on both sides:

3 - 5/2 = 2 - 5/2

3 = 2
Can you equate 3 and 2 by some mathematics logic?

See this illustration:

-6 = -6

9-15 = 4-10

9-15+25/4 = 4-10+25/4

Changing the order

9+25/4-15 = 4+25/4-10

(this is just like a square + b square - two a b = (a-b)square.)

Here a = 3, b=5/2 for L.H.S and a =2, b=5/2 for R.H.S.

So it can be expressed as follows:

(3-5/2)(3-5/2) = (2-5/2)(2-5/2)

Taking positive square root on both sides:

3 - 5/2 = 2 - 5/2

3 = 2
-----------------------------------------------------------------------------------------------